Pengaruh Kompetensi Pegawai terhadap Pengelolaan Arsip di Dinas Perpustakaan dan Kearsipan Kabupaten Bojonegoro - Hariyati, Tutik; Puspasari, Durinda (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to analyze the effect of employee competence on archive management at the Library and Archives Service of Bojonegoro Regency. This research is a quantitative research. Data collection techniques used are questionnaires and interviews. The population in this study were employees at the Library and Archives Service of Bojonegoro Regency, amounting to 40 people. The sampling technique used is saturated sampling, where the number of samples used is the same as the total population of 40 people. The instrument test in this study consisted of a validity test and a reliability test. The data analysis techniques used in this study are: 1) classical assumption test consisting of normality test and heteroscedasticity test; 2) hypothesis testing using simple linear regression. The results showed that there was a significant influence of employee competence on archive management at the Library and Archives Service of Bojonegoro Regency as evidenced by the sig value 0.000 <0.05 and tcount 5,619 > ttable 2,021 so it can be concluded that employee competence has a significant influence on archive management.